ANALISIS KESESUAIAN BUKU SISWA KELAS IV BERBASIS KURIKULUM 2013 - Bernadine Ajeng Indriasari (Jurnal PGSD Musi, 2021)
The aim of this research is to know fourth grade student book based on Curricullum 2013 in theme “Pahlawanku” subtheme “Pahlawanku Kebanggaanku” on lesson three with core competencies, learning objectives, indicators, materials, tool and learning resources. This section is ninth fragment from eighteen analyze from fourth grade student book based on Curricullum 2013 on theme “Pahlawanku” subtheme “Pahlawanku Kebangganku”. This research using qualitative descriptive method by analyze document are fourth grade student book based on Curricullum 2013 on theme “Pahlawanku” and fourth grade teacher book based on Curricullum 2013. The analyze revolves on the rule of Ministry of Education and Culture, and article discussing about the implementation of Curricullum 2013 and article from Badan Nasional Standar Pendidikan (BSNP) website. The result of this research are found that there is PJOK indicators not in accordance with core competencies. There is learning materials not in accordance with learning activities. There is no tools and learning resources adding. The conclusions of this research is fourth grade student book on theme “Pahlawanku” needs much improved with the discrepancies that found in lesson three on subtheme “Pahlawanku Kebanggaanku”.